2006
DOI: 10.1099/mic.0.28412-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel class of CoA-transferase involved in short-chain fatty acid metabolism in butyrate-producing human colonic bacteria

Abstract: Bacterial butyryl-CoA CoA-transferase activity plays a key role in butyrate formation in the human colon, but the enzyme and corresponding gene responsible for this activity have not previously been identified. A novel CoA-transferase gene is described from the colonic bacterium Roseburia sp. A2-183, with similarity to acetyl-CoA hydrolase as well as 4-hydroxybutyrate CoA-transferase sequences. The gene product, overexpressed in an Escherichia coli lysate, showed activity with butyryl-CoA and to a lesser degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
81
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 40 publications
9
81
0
Order By: Relevance
“…These two groups of bacteria are significant members of the gut ecosystem and play central roles in maintaining functions that are essential to gut health (2,11). The phylum Bacteroidetes has been shown to contribute to the host's ability to degrade indigestible carbohydrates (2), while the members of the order Clostridiales have been documented as being the main producers of short-chain fatty acids, such as butyrate, in the gut (8). Thus, any changes in these keystone groups may impact on the total bacterial communities' capacity to provide beneficial functions to the host.…”
Section: Discussionmentioning
confidence: 99%
“…These two groups of bacteria are significant members of the gut ecosystem and play central roles in maintaining functions that are essential to gut health (2,11). The phylum Bacteroidetes has been shown to contribute to the host's ability to degrade indigestible carbohydrates (2), while the members of the order Clostridiales have been documented as being the main producers of short-chain fatty acids, such as butyrate, in the gut (8). Thus, any changes in these keystone groups may impact on the total bacterial communities' capacity to provide beneficial functions to the host.…”
Section: Discussionmentioning
confidence: 99%
“…Although a gene encoding a propionyl CoA transferase could not be detected in R. inulinivorans by use of degenerate PCR primers (P. Louis, personal communication), the bacterium does possess a butyryl CoA transferase (27), and the same enzyme in a related Roseburia sp. can use either propionate or butyrate as a cosubstrate (6).…”
Section: Discussionmentioning
confidence: 99%
“…This transferase is thought to be especially advantageous in the colonic ecosystem due to the high levels of acetate, allowing butyrate producers to take up and use a waste product of other microbes (15). Many studies have suggested that the majority of butyrate production in hindgut fermenters is the product of But enzyme activity, including in swine (13,14,(16)(17)(18). It should be noted that previous work has suggested that not all enzymes capable of But activity are homologous.…”
mentioning
confidence: 99%
“…The sequence variation for the but gene family is poorly defined and currently includes closely related transferases that have differing substrate preferences (16,17,20). The FunGene But protein database is a large repository of But-like protein sequences and is an excellent resource; however, it contains But proteins and similar transferases that have distinct substrate specificities.…”
mentioning
confidence: 99%